ARTISTIC AND AESTHETIC CANVAS OF NAU SPACE ORGANIZATION - Bolotov, Georgiy; Pershakov, Valeriy; Pylypenko, Oleksandr (Proceedings of National Aviation University (archive), 2020)
The paper considers the harmonization aspects of the architectural environment of the National Aviation University (NAU) by creating a powerful artistic and aesthetic canvas, which represents architectural and artistic interpretation of the buildings, rational landscape organization of its territory, plastic-decorative unity of the interior space, and artistic-decorative symbolism in the business life.